The Effect of Brainstorming on Loneliness Level among Elderly - M.Elyas Arif Budiman; Zidni Nuris Yuhbaba; Guruh Wirasakti; Wike Rosalini (Nursing and Health Sciences Journal (NHSJ), 2021)
Loneliness is an unpleasant subjective experience for the elderly when several important criteria in social relationships are hampered or not met. Loneliness in the elderly can be overcome with positive social support. The purpose of the study was to determine the effect of social support with the brainstorming method on the level of loneliness in the elderly. This study uses a pre-experiment with a pre-test-post-test design approach. The population is elderly who live in elderly social services and have certain characteristics, amounting to 66 people. The sample amounted to 33 people with sampling using purposive sampling technique. In this study, brainstorming was given 2 times for 2 weeks with a duration of 40 minutes. The data collection method used the R-UCLA Loneliness Scale and then the data were analyzed using the Wilcoxon Signed Rank Test statistical test with the results of p value = 0.000 < α = 0.05. The conclusion in this study that social support with the brainstorming method has an influence on the level of loneliness because in the brainstorming process the elderly are able to improve interpersonal communication and create a harmonious group, so in this study shows that social support is one of the actions that can reduce loneliness in the elderly